Effect of liming and N fertilization on growth, macronutrient content and uptake by mixed stands of three clovers and timothy - Jokinen, Raili (Agricultural and Food Science, 1985)
Mixed stands of clovers and timothy grew well in unlimed (Ca0) acid soil (pH(CaCl2) 4.8). The highest total yield of red clover-timothy was obtained at a low lime level (Ca1 = 12g /pot CaCO3). The yield of red clover alone responded to liming similarly. The reducing effect of N fertilization (2000 mg/pot N as NH4NO3) on the yield of clovers was greatest in the first growing season (cuts 1 to 4) without lime, and in the second growing season (cuts 5 to 7) with lime (Ca1 = 12g /pot, Ca2 = 24g/pot). Liming without N fertilization promoted the growth of timothy only in the two first cuts; N fertilization increased the yield at all lime levels. Liming increased the Ca content of clovers, but there were no differences between lime levels. Mg and K showed a decreasing trend. N fertilization did not affect the nutrient content of clovers. A good quality of clover yield reguired adequate amounts of other fertilizations than N. In timothy, the Ca content increased slightly at all lime levels; the N and K contents increased by N fertilization. The N uptake by red clover was highest at the Ca, level, by white clover and alsike clover at the Ca0 level. The proportion of clover was larger than that of timothy of the uptake of N, P, Ca and Mg. When N was applied, the uptake of K showed an opposite direction.